2000
DOI: 10.1002/1097-4636(2000)53:4<314::aid-jbm5>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mechanical properties of all-ceramic alumina dental crowns prepared from aqueous- and non-aqueous-based tape casting

Abstract: Alumina-glass dental composites were prepared by aqueous- and non-aqueous-based tape casting and sintering at 1120 degrees C, followed by glass infiltration at 1100 degrees C. Flexural strength and fracture toughness of the composites were investigated in terms of influence of tape constituents, namely, alumina powder, binder, and plasticizer on the mechanical properties. For the alumina-glass composites prepared from the aqueous-based tapes, both strength and toughness increased with increasing alumina fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The preparation of β‐TCP sheets using the tape‐casting technique is influenced by various processing parameters, such as the ratio of binder/plasticizer/solvent, casting speed, blade gaps, etc. Kim et al22 reported that the mechanical properties of alumina‐glass dental composite prepared by using the tape‐casting method were influenced by the ratio of alumina powder, binder, and plasticizer. Tok et al17 found that a higher degree of accuracy in tape thickness can be obtained by casting at a lower casting speed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The preparation of β‐TCP sheets using the tape‐casting technique is influenced by various processing parameters, such as the ratio of binder/plasticizer/solvent, casting speed, blade gaps, etc. Kim et al22 reported that the mechanical properties of alumina‐glass dental composite prepared by using the tape‐casting method were influenced by the ratio of alumina powder, binder, and plasticizer. Tok et al17 found that a higher degree of accuracy in tape thickness can be obtained by casting at a lower casting speed.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersant used in the present first slurry consists primarily of poly(acrylic acid). The binder and plasticizer in the second slurry consist primarily of poly(acrylic acid)19 and polyethylene glycol,20, 22 respectively. There are several reports related to the composition of dispersant, binder, and plasticizer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 For further reduction of the shrinkage, it is essential to lower both the presintering and the infiltration temperature. Many studies on melt-infiltrated alumina glass composites have been reported in literature, 3,4,[9][10][11] but all the glasses used in these investigations are based on the lanthanum-aluminosilicate glass, 7 where a minimum infiltration temperature of 1100 • C is required. Therefore, in order to reduce the fabrication temperature, it is necessary to develop new glasses that allow infiltrating alumina at lower temperature.…”
Section: Introductionmentioning
confidence: 99%